The multi-faceted effects of technology-driven productivity surge in the crop & livestock sector in Greece: Evidence from the FABLE Calculator - Phoebe Koundouri; Konstantinos Dellis; Olympia Miziaki (PLoS ONE, 2026)
This paper the effects of a technology-driven increase in crop and livestock productivity on key agricultural, land-use, and environmental indicators in Greece, using the FABLE (Food, Agriculture, Biodiversity, Land Use, and Energy) Calculator. Through empirical evidence and sophisticated modelling techniques, we analyze the intricate interplay between agricultural productivity and environmental sustainability. Our scenario-based projections show that higher agricultural productivity substantially reduces greenhouse gas emissions, primarily through lower livestock emissions, diminished pressure on pastureland, and increased emission withdrawals from land-use changes. Enhancing productivity in the livestock and crop sector reduces GHG emissions from agriculture by 29% until 2030 and 62% until 2050, compared to a business-as-usual scenario. The result is amplified when we embed the productivity surge in a holistic transformational strategy following Greece’s national commitment including a shift to healthy dietary consumption. Moreover, costs decline markedly, by almost 50% in the long run, driven mainly by the reduction in pesticide use. In addition to its empirical findings, this paper delineates policy recommendations to support cutting-edge technologies within the Greek agricultural sector, focusing on horizontal and vertical measures. We highlight key precision agriculture technologies that align with current trends in Greece, particularly in the areas of drone applications, advanced sensors, and variable rate technology, alongside innovations in precision livestock management. Overall, our findings demonstrate that boosting agricultural productivity can generate a double dividend—lower emissions and enhanced competitiveness—particularly when supported by holistic policy measures.